9.3% Efficient Flexible Cu2ZnSn(S, Se)4 Solar Cells with High‐Quality Interfaces via Ultrathin CdS and Zn0.8Sn0.2O Buffer Layers. Issue 10 (29th July 2022) - Lin, Beibei; Sun, Quanzhen; Zhang, Caixia; Deng, Hui; Xie, Weihao; Tang, Jianlong; Zheng, Qiao; Wu, Jionghua; Zhou, Haifang; Cheng, Shuying
Abstract : The buffer layer plays a critical role in high‐performance flexible Cu2 ZnSn(S, Se)4 (CZTSSe) solar cell. The conventional CdS buffer layer causes the photoelectric performance loss and the pollution of toxic Cd. Herein, the ultrathin CdS and Zn0.8 Sn0.2 O (ZTO) buffer layer engineering is proposed to reduce interface recombination and Cd content. An ultrathin CdS layer acts as the interface passivation layer to protect the CZTSSe layer and passivate its surface defects. To solve the problems of decreased carrier collection capacity caused by thinning the CdS layer, the ZTO layer with low resistivity and high carrier concentration is obtained by doping Sn into the ZnO layer. The systematic study indicates that the ultrathin CdS and ZTO buffer layers‐based solar cells realize high‐quality interface and band matching. Ultimately, 9.3% efficiency of the ultrathin CdS and ZTO‐based solar cell with 448 mV open‐circuit voltage is obtained, which is higher than that of the standard CdS buffer layer‐based device (8.5% with 419 mV). The study provides a new idea for achieving efficient flexible CZTSSe solar cells through heterojunction interface management. Abstract : The ultrathin CdS and Zn0.8 Sn0.2 O buffer layers are applied to the flexible Cu2 ZnSn(S, Se)4 (CZTSSe) solar cells to solve serious interface recombination and high Cd content caused by CdS buffer layer. A 9.3% efficiency for flexible device is achieved, which is higher than that of the standard device (8.5%). The study exhibits effective interface management for flexible CZTSSe solar cells.